Polymer Materials in Biomedical Application - Raza, Faisal; Nugraha, Bramasta (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Recently, the development of polymeric materials for biomedical applications has advanced significantly. Polymeric materials are favored in the development of therapeutic devices, including temporary implants and three-dimensional scaffolds for tissue engineering and in vitro disease modelling.Further advancements have also occurred in the utilization of polymeric materials for pharmacological applications, such as delivery vehicles for drug release.We would like to invite you to contribute to this Special Issue. Research topics of interest include, but are not limited to, recent advances related to 3D cell culture, biomaterials, tissue engineering, disease modelling, hydrogel, organoids, drug discovery, bioimaging, cardio-renal, metabolic disease, and stem cell biology.